2015
DOI: 10.1021/cs501963v
|View full text |Cite
|
Sign up to set email alerts
|

A Mn Bipyrimidine Catalyst Predicted To Reduce CO2 at Lower Overpotential

Abstract: Computational MethodsDensity functional theory (DFT) calculations for geometry optimizations, electronic energy, solvation energy, and vibrational frequencies were performed using the (U)B3LYP hybrid exchange-correlation functional 1 with the D3 dispersion correction, 2 as implemented in the Jaguar software version 7.9. 3 Solvation effects were modeled using the Poisson-Boltzmann continuum (PBF) approximation 4 for acetonitrile (ε = 37.5, r = 2.18).Geometry optimizations were performed in the gas phase (for CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 47 publications
6
83
0
2
Order By: Relevance
“…Currently, much of the literature regarding molecular electrochemical activation of CO 2 still continues to explore the catalytic properties of the heavier members of Group‐7 (Re), Group‐8 (Ru and Os) and Group‐9 (Rh, and Ir) triads. These “first‐generation” electrocatalysts must be phased out; encouragingly, cheaper alternatives exist within the same groups – Mn substituting Re, Fe substituting Ru and Os, and Co substituting Rh and Ir . However, the community's focus on late transition metals is leaving the Group‐6 metals (Cr, Mo, W) rather neglected, despite the high potential for the comparatively abundant metal triad to function as both high‐performance alternatives to the noble metals and photostable alternatives to the hot‐topic manganese carbonyls .…”
Section: Methodsmentioning
confidence: 99%
“…Currently, much of the literature regarding molecular electrochemical activation of CO 2 still continues to explore the catalytic properties of the heavier members of Group‐7 (Re), Group‐8 (Ru and Os) and Group‐9 (Rh, and Ir) triads. These “first‐generation” electrocatalysts must be phased out; encouragingly, cheaper alternatives exist within the same groups – Mn substituting Re, Fe substituting Ru and Os, and Co substituting Rh and Ir . However, the community's focus on late transition metals is leaving the Group‐6 metals (Cr, Mo, W) rather neglected, despite the high potential for the comparatively abundant metal triad to function as both high‐performance alternatives to the noble metals and photostable alternatives to the hot‐topic manganese carbonyls .…”
Section: Methodsmentioning
confidence: 99%
“…In particular, this change should affect the energy of the LUMO, the reduction potential, and catalytic activity. [23][24][25][26][27][28][29][30][31][32][33] Introducing steric bulk 23,25 to prevent unwanted reactions of the catalytic species, including dimerization as either Mn Mn, 9 or C(imino) C(imino) bound species, 21 whilst at the same time reducing the risk of increased overpotential is a challenging task. Molecular designs that allow for steric and electronic effects to be decoupled are required.…”
Section: Chartmentioning
confidence: 99%
“…However, coordination of CO 2 to the 5-coordinate anion produces a stable species which must be reduced at considerably more negative potentials 27 in order for catalysis to be observed. It has recently been shown that in the presence of a Lewis acid, Mg 2+ , 7,28 the catalytic overpotential 29 is decreased by approximately 400 mV.…”
mentioning
confidence: 99%
“…Rhenium bipyridine complexes (Re(bpy)(CO) 3 Cl and its derivatives) 104 – 108 and manganese complexes (Mn(bpy)(CO) 3 Br and its derivatives) 109 114 are known to act as catalysts for electrocatalytic reduction of CO 2 to CO. The catalytic mechanisms have been investigated extensively using various spectroscopic methods including UV/Vis absorption and pulsed-EPR techniques (2P-ESEEM and HYSCORE) combined with DFT calculations.…”
Section: Electrocatalytic Reduction Of Co 2 To Co mentioning
confidence: 99%